THE USE OF INDIVIDUAL PROTECTION EQUIPMENT AMONG THE NURSING STAFF OF A PUBLIC HOSPITAL - Nathanye Crystal Stanganelli; Renata Perfeito Ribeiro; Caroline Vieira Claudio; Júlia Trevisan Martins; Patricia Helena Vivan Ribeiro; Benedita Gonçalves de Assis Ribeiro (Universidade Federal do Paraná, 2015)
The objective was to identify the use of personal protection equipment by nursing workers during procedures which expose them to biological fluids. It was observational, descriptive and transversal research, with a quantitative approach, undertaken in a public hospital in the state of Paraná, in January - May 2014, using nonparticipant and intentional observation of 201 procedures through the use of a checklist. It was ascertained that, in the Surgical Center, procedure gloves (97%) obtained the greatest adherence, but that closed shoes and eye protection were not used on any occasion. In the Central Sterile Services Department, no worker used the procedure gloves, either rubber or heat-resistant, although the surgical mask (44.4%) had the greatest adherence in the cleaning room. In the Intensive Care Units and Emergency Room, the procedure gloves were used (100%), although adherence to the eye protection was low (0.86%). The nursing staff did not use all the equipment stipulated by legislation during their activities.